The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1155/2016/6805485
|View full text |Cite
|
Sign up to set email alerts
|

Child Welfare Deprivation in Rural Nigeria: A Counting Approach

Abstract: The study applies the counting approach to explain the deprivation concept among children under 5 years of age using the 2008 DHS data. Five dimensions of deprivation were used: safe drinking water, sanitation, housing, health, and nutrition largely recognized in the SDGs. In all, a total of 13561 children were sampled. About half of the children were males with a mean age of 28.27 months old. The assessment of dimensional deprivation showed that children are most deprived in sanitation, health, and access to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
(30 reference statements)
1
2
0
Order By: Relevance
“…With availability of potable water, the respondents are not likely to be predisposed to water-borne illnesses. This view is in tandem with the findings of Popoola and Adeoti (2016) who reported that access to adequate water supply and adequate sanitation services have a direct influence on children's health, education, wellbeing, and social development.…”
Section: Resultssupporting
confidence: 69%
“…With availability of potable water, the respondents are not likely to be predisposed to water-borne illnesses. This view is in tandem with the findings of Popoola and Adeoti (2016) who reported that access to adequate water supply and adequate sanitation services have a direct influence on children's health, education, wellbeing, and social development.…”
Section: Resultssupporting
confidence: 69%
“…We find that children in the rural areas of Yé were more likely to suffer from multidimensional poverty compared to the urban children in Dédougou. Supportive findings from literature highlight this assertion of uneven geographical inequality in terms of distribution of economic resources [57,58]. Living in rural areas for example, with low job opportunities and high concentration of poor individuals increases the tendency of a child growing up poor.…”
Section: Discussionmentioning
confidence: 91%
“…UNICEF Nigeria is tackling the problems head-on with child survival programs such as neonatal care, appropriate nutrition, clean water and sanitation, and necessary healthcare to advocate for and facilitate child development programs, i.e., child education, child protection, and child rights. In evidencebased practice, UNICEF and several other econometric studies (for example, Okpukpara, et al [65], Ojelabi and Oyewole [66], and Popoola and Adeoti [67]) have advocated for the holistic implementation of childcare programs. In advanced countries, these programs are realized through social work with families and children, school social work, and social work services in national social security organizations, particularly for physically and socially disadvantaged children.…”
Section: What International Organizations' Models Are Currently Influ...mentioning
confidence: 99%